Concurrent determination of U, Np, Pu, Am, and Cm in clay systems at ultra-trace levels with accelerator mass spectrometry. Issue 8 (6th July 2022) - Glückman, Daniel; Quinto, Francesca; Hain, Karin; Joseph, Claudia; Montoya, Vanessa; Steier, Peter; Geckeis, Horst
Abstract : The present study demonstrates the analytical capability of AMS in clay matrices by the concurrent determination of the actinide nuclides 233 U, 237 Np, 244 Pu, 243 Am, and 248 Cm down to ≈0.07 fg per sample. Abstract : The geochemistry of actinides under reducing conditions in a deep geological nuclear waste repository is characterized by low solubility and strong sorption to mineral surfaces. The quantification of actinide migration ( i.e. diffusion) at resulting concentration levels requires an analytical method able to determine actinide concentrations down to ultra-trace levels (≈fg g −1 ). In the actual study, such an analytical procedure was tested by using accelerator mass spectrometry (AMS), one of the very few analytical techniques that can presently meet those requirements. Specimens simulating the sample matrix representative for a diffusion experiment in natural clay rock were produced by spiking clay rock powders (Opalinus Clay or Callovo-Oxfordian Clay) and aliquots of corresponding pore waters with the actinide nuclides 233 U, 237 Np, 244 Pu, and 248 Cm in amounts ranging from approximately 3 × 10 −19 to 5 × 10 −15 mol per sample (≈0.07–1000 fg per sample). The actinide nuclides were separated as group via Fe(OH)3 co-precipitation and then analyzed sequentially with AMS. During such analysis a decrease in count rates by up to a factor of 6 was observed in high-matrix clay rock samples compared to low-matrix standard solutions. Since the chemical yield of the actinides in the Fe(OH)3 co-precipitation step prior to analysis turned out to be quantitative, this observation must originate from a reduction of the sputter rate of the actinide nuclides in the AMS ion source, which can be described partly as a dilution effect. By determining chemical-ionization-yield factors, suitable non-isotopic tracers were identified for 237 Np and 243 Am. This allowed for the concurrent determination of all actinide nuclides at levels down to 3 × 10 −19 mol per sample. Different actinides in a deep geological formation may be present in concentration ranges differing by orders of magnitude depending on their chemical form and solubility. Such concentration spreads were simulated by preparing clay rock/pore water samples where each individual sample contained 233 U, 237 Np, 244 Pu, 243 Am, and 248 Cm at quantities ranging from approximately 3 × 10 −19 to 4 × 10 −15 mol per sample. The presented sample preparation procedure, in combination with the extraordinary detection sensitivity of AMS allows for the simultaneous determination of diffusion profiles of several actinides at ultra-trace levels within one experiment.